MATHEMATICS AND SCIENCE TEACHERS’ PERCEPTIONS AND COMMUNICATION STRATEGIES ON THE USE OF ENGLISH AS A MEDIUM OF INSTRUCTION AT SMP NEGERI 1 DENPASAR - Sudiatmika, I Ketut; Nitiasih, Putu Kerti; Suarnajaya, I Wayan (Jurnal Pendidikan Bahasa Inggris Indonesia, 2013)
Abstract This study aimed at investigating the use of English as a medium of instruction (EMI) at Pre-International Standard School (RSBI) at SMP N 1 Denpasar. It includes the mathematics and science teachers? perception, the frequency of the use of English, and the communication strategies used by mathematics and science teachers. The subjects of the study were mathematics and science teachers at SMP N 1 Denpasar of grade eight. Semi-structured interview and close questionnaire were applied to gather the data of mathematics and science teachers? perception. The frequency of English and communication strategies used by the mathematics and science teachers were gathered by recording the instructional process. The findings of the study show that the mathematics and biology teachers had a good perception, but physics teacher had average perception toward the use of English as a medium of instruction. However, the proportion of English used as a medium of instruction at SMP N 1 Denpasar has not fulfilled the basic requirement of Pre-International Standard School (RSBI). Even, in its sixth year of the program implementation, the science teachers have not implemented 100% the bilingual teaching and learning process. The average percentage of English used by the Mathematics, Biology, and Physics teachers is 84.50 %, 13.72%, and 0% respectively. The data analysis also revealed that there were five types of communication strategy applied by the mathematics and science teachers, namely: language switching, pausing, use of non linguistic resources, clarification check, and comprehension check.   Key words: bilingual class, teachers? perception, English frequency, communication strategies